PENGARUH VARIASI LATIHAN TERHADAP PENINGKATAN KETERAMPILAN BERMAIN SEPAK BOLA PADA CLUB PUTRA BAJA FC TAHUN 2017 - Quddus, Abbdul; dinata, karno; Daniyantara, Didik (Jurnal Porkes, 2018)
In this study aims to determine whether or not the influence of exercise variation on the Improvement of Football Playing Skills at Club Puta Baya FC 2017? ". In this research the method used to obtain the data is the method of documentation, and the method of action test, which became the population is Club Football Puta Baya FC 2017 amounted to 23 people using population study technique, that is the entire population sampled. The research design used in the study using One group pre-test post design, in this design there is no control group and the subjects are not placed randomly, pre-test before treatment, and post-test after treatment. The instruments in the implementation of this research is to test the skills of playing football (passing, heading, shotting, dribbling) and then carry out the treatment or variation of the exercise. Method of data analysis using statistical analysis by using t-test formula as test of research hypothesis. The result of the analysis obtained "t" counted 26,06 for the variation of practice to the skill of playing soccer and while the value of "t" table equal to 1,717 ("t" count ? "t" table) with degree of freedom (df) = N-1 = 20-1 = 19 and a significance level of 5%. This fact proves that "t" counts the "t" table. So it can be argued that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is